Congenital Cystic Lung Lesions: Redefining the Natural Distribution of Subtypes and Assessing the Risk of Malignancy. (January 2019) - Pogoriler, Jennifer; Swarr, Daniel; Kreiger, Portia; Adzick, N. Scott; Peranteau, William
Abstract : Asymptomatic cystic lung lesions—congenital pulmonary airway malformations (CPAMs), sequestrations, and bronchogenic cysts—are commonly diagnosed prenatally. Indications to resect are to eliminate risk of malignancy or infection. CPAMs consist of a spectrum of malformations, with type 1 historically considered the most common. Mucinous cell clusters, seen almost exclusively in type 1, are premalignant lesions at risk for progression to mucinous adenocarcinoma. We reviewed and classified 2.5 years of consecutive, prenatally diagnosed lesions as extralobar sequestration, intralobar sequestration, type 1 CPAM, type 2 CPAM/bronchial atresia, or "other" to determine the distribution of lesion types and risk of malignancy. One hundred eighty-four lesions in 174 patients showed type 1 CPAM to be least common subtype. Type 1 CPAMs had more severe presentation, infrequently had features of obstruction, and usually had cysts ≥2 cm. Fifteen of eighteen type 1 CPAMs had mucinous cell clusters (total risk, 8%), with mucous cells outside main cyst in 12/15. No pleuropulmonary blastomas were identified. Additional historic cases were reviewed to further evaluate risk of malignancy. Over 14 years, 28 infants with fetal/type 1 lesions were identified, with clusters of mucinous cells in 75% of cases. A total of 9 pleuropulmonary blastomas were diagnosed in 6 patients over 16 years. Contrary to historical studies, type 1 CPAMs are much less common than type 2, likely related to detection of asymptomatic lesions prenatally. A majority of type 1 CPAMs contain mucinous cell clusters. This data is useful in management of patients in centers that do not resect asymptomatic lesions.